Uptake, accumulation and gene response of Sb(Ⅴ) in Arabidopsis thaliana - Ziyi Dong; Mengchang He; Chunye Lin; Wei Ouyang; Xitao Liu (Ecotoxicology and Environmental Safety)
Antimony (Sb) is a toxic pollutant, with Sb(V) being one of its main forms in the environment, but the process and mechanism of plant uptake of Sb(V) remain unclear. To investigate the process of Sb(V) uptake by plants, Arabidopsis thaliana plants were exposed to water culture media supplemented with different Sb(V) concentrations. The distribution, content, and forms of Sb(V) in Arabidopsis roots, and the accumulation and fixation of Sb(V) in Arabidopsis plants were studied. In addition, inhibitor experiments and analyses of gene expression changes were conducted to elucidate the underlying mechanism of its toxicity. Sb(V) entering the roots was mainly adsorbed on the cell wall, and the Sb(V) content in both apoplastic solution and symplastic solution increased with increasing external Sb(V) concentration. Sb(V) concentration in apoplast and symplast were approximately linearly correlated (R2=0.980), indicating low affinity of cells for Sb(V) absorption. Moreover, uncouplers significantly inhibited the entry of Sb(V) into the symplast, suggesting that the transmembrane transport of Sb(V) is energy-consuming. Sb(V) entering the cell could be partially reduced to Sb(III), and significant changes in glutathione metabolism gene expression were detected, indicating the important role of glutathione metabolism in the detoxification of Sb(V). From the perspective of the whole plant, although Sb(V) is absorbed by the roots, it is mainly fixed in the leaves and stems. This study revealed the pattern of Sb(V) uptake by plants and elucidated the mechanism of Sb(V) uptake by plants from the perspectives of kinetics, physiology, and genetics.